Commonly reported isokinetic parameters do not reveal long-term strength deficits of the Triceps surae complex following operative treatment of Achilles tendon rupture. (5th March 2020) - Walker, Josh; Nicholson, Gareth; Jongerius, Nils; Parelkar, Parag; Harris, Nick; Bissas, Athanassios
Abstract: Isokinetic strength assessments are common outcome measures following operatively treated Achilles tendon (AT) ruptures. However, there is a lack of clarity on whether commonly reported outcome measures (such as peak joint moment) are sufficient to describe the extent of long-term functional deficits following AT rupture and repair. The present study conducted a comprehensive isokinetic evaluation of the Triceps surae complex in 12 participants who previously underwent AT rupture and repair. Testing occurred 4.4 (±2.6) years following surgery, and consisted of maximal isokinetic strength assessments of the plantarflexors at two angular velocities (30 and 60°∙s −1 ) with the knee in flexed and straight positions. Differences between injured and non-injured limbs were tested through discrete and statistical parametric mapping analysis. Average joint moment showed significant main effects between injured and non-injured limbs, but common isokinetic parameters such as peak moment and angle of peak moment did not. The normalised moment curves showed a significant main effect of limb, angular velocity and knee joint position on joint moment throughout different portions of the range of motion. Temporal analysis revealed a significantly greater ability of the non-injured limb to sustain plantarflexor moments across a range of testing conditions. Participants who had undergone operative treatment of AT ruptures did not display inter-limb differences in discrete isokinetic strength outcomes that are often used in the literature. Instead, temporal analyses were required to highlight the reduced capacity of the injured limb to generate end-range joint moments and to sustain higher levels of joint moment for longer periods.